Interventricular septal dissection in a patient with atrial septal defect and pulmonary hypertension - Personaldi, Personaldi; Dinarti, Lucia Kris; Marsam, Real Kusumanjaya; Mumpuni, Hasanah (Universitas Brawijaya, 2025)
Background: Interventricular septal dissection (IVSD) is a sporadic disorder. Previous literature has reported cases of IVSD caused by sinus valsalva aneurysms, post-myocardial infarction patients, congenital abnormalities, or post-thoracic trauma. However, no prior literature has reported IVSD cases caused by an atrial septal defect (ASD) accompanied by pulmonary hypertension. This case report aims to initiate the discussion of recognizing the association between ASD-PH and IVSD. Case presentation: A 48-year-old female with ASD was brought to Dr. Sardjito General Hospital with complaints of fatigue. In 2013, the patient experienced attacks of hemoptysis, which was then revealed to be caused by an increase in pulmonary pressure. Transthoracic echocardiography (TTE) examination results concluded that the patient had a high probability of pulmonary hypertension (PH), secundum atrial septal defect (ASD), which was 22-25 mm in diameter, a bidirectional shunt, and mid-apical interventricular septum dissection with flow. The patient underwent a right heart catheterization examination on September 3rd, 2015, at Dr. Sardjito General Hospital and was confirmed with pulmonary hypertension. The patient underwent computed topography (CT) scan with contrast on March, 2024, for evaluation, where we found a rupture of the interventricular septal muscle. Conclusion: The incidence of interventricular septal dissection is rare. Various causes are suspected, such as sinus of Valsalva rupture, post-myocardial infarction events, or associated congenital abnormalities. From this report, we present an IVSD case that is concurrent with ASD-PH. ASD and pulmonary hypertension, through combination of myocardial injury and hypertension, can cause interventricular septal dissection.